Relationship between emotional intelligence and self-regulated learning of students in Biology subjects - Mustofa, Romy Faisal; Rachmawati, Mega; Nuryadin, Egi (Universitas Malikussaleh, 2022)
This study aims to determine the relationship between emotional intelligence and self-regulated learning of students in biology subjects in class XI MIPA SMA Negeri 1 Tasikmalaya. The research method used is a correlation. The population in this study was the entire class XI MIPA SMA Negeri 1 Tasikmalaya, amounting to 272 students. The research sample was taken using a purposive sampling technique as many as two classes, namely class XI MIPA 6 and XI MIPA 7 with 39 students who filled out the questionnaire. The data analysis technique used is a simple correlation test. The results of the study showed that there was a relationship between emotional intelligence and students' self-regulated learning. For the relationship between emotional intelligence and self-regulated learning, R is 0.568, which means it has a moderate level of relationship. The coefficient of determination of the emotional intelligence variable on the self-regulated learning variable is R2, which is 0.322, which means that the emotional intelligence variable contributes 32.3% to the self-regulated learning of students. Method, one of them by counseling approach of Cognitive Behaviour Therapy (CBT) using guided imagery technique.